Aucklandia lappa Decne.: a review of its botany, cultivation, ethnopharmacology, phytochemistry, pharmacology, and practical applications - Chen, Jing; Zhao, Zilong; Lin, Lihua; Wang, Guangyao; Yang, Haixia; Wang, Xinghua (Frontiers in Pharmacology, 2025)
Aucklandia lappa Decne. (ALD), a synonym of Saussurea costus (Falc.) Lipsch., is a traditional Chinese medicinal herb extensively cultivated in China. Aucklandiae Radix (AR, known as “Muxiang” in China), derived from the dried root of ALD, holds a significant position in the clinical application of traditional Chinese medicine, encompassing the enhancement of gastrointestinal motility, antibacterial properties, and antitumor activities. Notably, AR possesses a complex and diverse chemical composition, with costunolide and dehydrocostus lactone being its core active metabolites. This review provides an in-depth exploration of the biological characteristics, cultivation techniques, ethnopharmacology, phytochemistry, pharmacological activities, and processing techniques associated with ALD. To collect relevant research materials, the study systematically retrieved information from authoritative databases such as CNKI, PubMed, Elsevier, Web of Science, and SpringerLink, employing keywords including “cultivation,” “phytochemistry,” “pharmacology,” and the plant names “Aucklandia lappa Decne.,” “Saussurea costus (Falc.) Lipsch.,” or “Aucklandiae Radix.” Despite demonstrating remarkable pharmacological activities and potential for clinical applications, research on ALD still faces several challenges. For instance, its specific mechanisms of action in treating certain diseases remain incompletely understood, and multiple studies have indicated that ALD extracts may cause adverse reactions. Further in-depth research and systematic evaluation can facilitate the optimization of ALD practices to promote further research into its myriad applications.